Modelling the Impact of Emissions Trading on the Iberian Electricity Market - Tomé Saraiva (2006)
The main purpose of this project is the analysis of the impact of the European market for emissions trading on the integration of Portugal and Spain into an Iberian electricity market. The integration of Portugal and Spain in a single-market may change the technological combination currently used to generate electricity as the current generation structure was mainly planned under monopoly and it may not be adequate for a scenario of liberalization. Further, the impact of emissions trading on the daily clearing prices, and generation scheduling will have important impacts on the value of the different generation technologies, and even on the benefits of integration as a whole. In this paper we analyze, through simulating, how the interaction between emissions trading and the MIBEL may re-shape the landscape of electricity generation, looking at clearing prices and the value of the different technologies, and how both countries are likely to be affected by it.